1993
DOI: 10.1128/jcm.31.7.1695-1699.1993
|View full text |Cite|
|
Sign up to set email alerts
|

Ability of clinical laboratories to detect antimicrobial agent-resistant enterococci

Abstract: To test the ability of clinical laboratories to detect antimicrobial resistance among enterococci, we sent four vancomycin-resistant enterococcal strains and one 13-lactamase-producing enterococcus to all 93 nongovernment, hospital-based clinical laboratories in New Jersey; 76 (82%) participated in the study. Each organism was tested by the laboratory's routine antimicrobial susceptibility testing method. The proportion of laboratories that correctly reported that an isolate was resistant to vancomycin varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
80
2
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 23 publications
3
80
2
1
Order By: Relevance
“…Laboratories participating in our survey had no difficulty in detecting the low-level vancomycin resistance of E. faeciurn D366, regardless of the wide range of susceptibility testing methods used. In contrast, an earlier study showed that 71% of laboratories failed to detect vancomycin resistance in a strain of E. faecium with an MIC of 64 mg/L [20]. The improved current results probably reflect use of the 1992 NCCLS revised procedure.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Laboratories participating in our survey had no difficulty in detecting the low-level vancomycin resistance of E. faeciurn D366, regardless of the wide range of susceptibility testing methods used. In contrast, an earlier study showed that 71% of laboratories failed to detect vancomycin resistance in a strain of E. faecium with an MIC of 64 mg/L [20]. The improved current results probably reflect use of the 1992 NCCLS revised procedure.…”
Section: Discussioncontrasting
confidence: 60%
“…Microscan users reported the greatest percentage of discordant susceptible results (88%) followed by Vitek (46%) and the breakpoint agar dilution (46%) methods. Lack of sensitivity of the Microscan panels and lack of specificity of the Vitek cards to detect ampicillin resistance have been noted previously [6,20]. The disk diffusion method was the most reliable at detecting the ampicillin resistance, although 19% of participating laboratories did report a falsely susceptible result.…”
Section: Discussionmentioning
confidence: 81%
“…The disk diffusion results disagreed (false intermediate) with the results (resistant) of both other methods for only three isolates. Several studies have reported the inability of some susceptibility testing methods, especially automated systems and disk diffusion, to detect resistance to ,-lactams, aminoglycosides, and glycopeptides (9,16). On the other hand, our results indicate that the E test appears to be an acceptable alternative for testing enterococci against the antimicrobial VOL.…”
mentioning
confidence: 58%
“…E. faecium has been the most often isolated species and VanA has been the most often reported phenotype (7). Nonetheless, because of difficulties in detecting some VanB-type VRE (41,42) and because some studies have been designed to detect the high levels of resistance more characteristic of the VanA phenotype (24,25), VanB-type VRE could be more widespread than previously thought.…”
mentioning
confidence: 99%